A comparison between the use of interactional strategies by native Japanese and Singaporean Japanese speakers - Tan, Jia Xuan (Nanyang Technological University, 2020)
Although features of Japanese communication have gathered a lot of interest, there has been little research done on the use of these features in an intercultural situation, especially by non-native speakers of Japanese. The use of these features may reflect the speaker’s attitude and their intercultural competence in intercultural communication. This study aims to compare and identify the interactional strategies used by Singaporean Japanese speakers, as well as native Japanese speakers, and how this may be related to them being members of their respective cultural groups. Overall, it has been observed that while both Singaporean Japanese speakers and native Japanese speakers maintained the use of typical features of Japanese communication, they differed in the use of other features during intercultural communication. Findings from this paper can be beneficial in the development of intercultural competence in Singaporeans, which is an indispensable skill, especially in the workforce (Fitch, 2012). This study may also be one of the first few studies done on intercultural communication between Singaporean and native Japanese speakers in a peer group setting.